PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA THRIFT SHOP - Savira, Viola Swara Nadaranty; Ida Yulianti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The acceleration of the delivery of information both visually and text is a driving factor for the development of the fashion industry in Indonesia. Used clothes are no longer underestimated by the people of Indonesia. Not only ordinary people who do thrifting, but influencers in the clothing sector also choose this method. The objective of this research is to identify the effect of brand image, product quality, and price on customer’s decision to purchase from thrift shop. As the analysis uses numeral data and statistical processes, this study is categorized as quantitative research. Utilizing non-probability method and saturated sampling technique with the criteria of people who have ever made any purchase in Locaswara, 75 people were selected as the sample. The results of the data analysis performed in SPSS 25 indicate that brand image, product quality, and price partially have positive and significant effects on purchase decision. Furthermore, the result of the coefficient of regression suggests that product quality has the strongest influence on purchase decisions in Locaswara.